Does Word of Mouth Influence Tourists’ Decisions to Visit? The Mediating Role of Destination Brand Image - Nur Hidayatul Istiqomah; Emory Kosh Jr (Universitas Airlangga, 2026)
Background: Visitation decisions at religious tourism sites are substantially shaped by two interrelated factors: word-of-mouth (WOM) communication and destination brand image. Because WOM draws on personal experience rather than institutional promotion, potential visitors tend to regard it as a more trustworthy source of information, particularly when evaluating religious-historical sites such as Makam Sunan Bonang. Objective: Drawing on data from Makam Sunan Bonang in Tuban, Indonesia, this study investigates both the direct effect of WOM on visitation decisions and the extent to which the destination brand image mediates this relationship in the context of religious tourism. Method: The study adopted a quantitative design, applying Partial Least Squares Structural Equation Modeling (PLS-SEM) to survey data collected through structured questionnaires administered to 170 pilgrims at the Sunan Bonang site in 2024, thereby meeting the minimum sample threshold for PLS-SEM. Results: WOM exerted a statistically significant positive influence on both visitation decisions and destination brand image. Destination brand image, in turn, significantly predicted visitation decisions and partially mediated the WOM–visitation relationship. Together, the two predictors accounted for a substantial share of variance in visit intention. Conclusion: WOM and destination brand image are key determinants of visitation to religious historical sites such as Makam Sunan Bonang; WOM both directly influences visit decisions and enhances brand image, which in turn increases visitation intention. Keywords: Word of Mouth; Brand Image; Decision to Visit; Historical Tourism; Halal